Anticipating the bust: A new cyclical systemic risk indicator to assess the likelihood and severity of financial crises - Jan Hannes Lang; Cosimo Izzo; Stephan Fahr; Josef Ruzicka (European Central Bank (ECB), 2019)
This paper presents a tractable, transparent and broad-based domestic cyclical systemic risk indicator (d-SRI) that captures risks stemming from domestic credit, real estate markets, asset prices, and external imbalances. The d-SRI increases on average several years before the onset of systemic financial crises, and its early warning properties for euro area countries are superior to those of the total credit-to-GDP gap. In addition, the level of the d-SRI around the start of financial crises is highly correlated with measures of subsequent crisis severity, such as GDP declines. Model estimates suggest that the d-SRI has significant predictive power for large declines in real GDP growth three to four years down the line, as it precedes shifts in the entire distribution of future real GDP growth and especially of its left tail. The d-SRI therefore provides useful information about both the probability and the likely cost of systemic financial crises many years in advance. Given its timely signals, the d-SRI is a useful analytical tool for macroprudential policymakers.
Keywords: G01; G17; C22; C54; 330; systemic risk; financial crises; early warning models; quantile regressions; local projections; GDP at risk